2017
DOI: 10.7554/elife.19837
|View full text |Cite
|
Sign up to set email alerts
|

The RFamide receptor DMSR-1 regulates stress-induced sleep in C. elegans

Abstract: In response to environments that cause cellular stress, animals engage in sleep behavior that facilitates recovery from the stress. In Caenorhabditis elegans, stress-induced sleep(SIS) is regulated by cytokine activation of the ALA neuron, which releases FLP-13 neuropeptides characterized by an amidated arginine-phenylalanine (RFamide) C-terminus motif. By performing an unbiased genetic screen for mutants that impair the somnogenic effects of FLP-13 neuropeptides, we identified the gene dmsr-1, which encodes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 53 publications
0
61
0
Order By: Relevance
“…We found that the onset, frequency, and duration of quiescent bouts in microfluidic chambers are unique compared to previously-reported sleep behaviors in adult C. elegans (Figure 1). While larval C. elegans display quiescence during lethargus [25], quiescence in adult worms occurs in only a few situations, such as after several hours of swimming [49,[51][52][53] or after exposure to extreme environmental conditions [40,44,45,54,55]. To determine how microfluidic-induced quiescence compares to the well-established "episodic behavior" that occurs in swimming animals and "stress-induced quiescence" that occurs from a 30 min heat shock, we quantified these behaviors using the same methods to analyze μSleep (Figure 1B-F).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that the onset, frequency, and duration of quiescent bouts in microfluidic chambers are unique compared to previously-reported sleep behaviors in adult C. elegans (Figure 1). While larval C. elegans display quiescence during lethargus [25], quiescence in adult worms occurs in only a few situations, such as after several hours of swimming [49,[51][52][53] or after exposure to extreme environmental conditions [40,44,45,54,55]. To determine how microfluidic-induced quiescence compares to the well-established "episodic behavior" that occurs in swimming animals and "stress-induced quiescence" that occurs from a 30 min heat shock, we quantified these behaviors using the same methods to analyze μSleep (Figure 1B-F).…”
Section: Resultsmentioning
confidence: 99%
“…Other well-known drivers of sleep are noxious environmental stressors, which we also tested in the context of our microfluidic chambers. Heat shock at temperatures greater than 30 °C is a common method to induce cellular stress and C. elegans sleep [34,40,44,45,54,72]. Although our standard μSleep assays were conducted at only 22 °C, we investigated whether these small changes from Tc could be a possible environmental regulator of quiescence.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Cellular stress causes the secretion of EGF, which activates EGF receptor signaling in a neuron called ALA . EGF activation leads to the secretion of multiple neuropeptides from ALA, which have both overlapping and distinct inhibitory functions on behavioral activity by binding to downstream receptors, likely involving a diffusional mechanism . It is not yet clear whether ALA presents a sleep‐active neuron in the sense that it depolarizes specifically during a sleep bout or whether it promotes sleep by a different mechanism.…”
Section: Genetically Removing Sleep In Model Systems: C Elegansmentioning
confidence: 99%
“…In addition, dopamine, tyramine, and octopamine influence behaviors associated with the presence or absence of food (Alkema et al, 2005;Chase et al, 2004;Horvitz et al, 1982;Sawin et al, 2000;Stern et al, 2017). The C. elegans sleep-like state is also strongly influenced by neuropeptides, including and ligands for the NPR-1 receptor (Choi et al, 2013;Iannacone et al, 2017;Nath et al, 2016;Nelson et al, 2014). Command-like neurons that release neuromodulators are capable of driving state changes: the serotonergic NSM neurons induce dwelling states (Flavell et al, 2013;Rhoades et al, 2019) and the peptidergic ALA neuron evokes a sleep-like state Nath et al, 2016;Nelson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%